خطاب الكراهية بين حرية التعبير والتجريم- دراسة على ضوء أحكام القانون الدولي- - حاجة, وافي (University of Eloued جامعة الوادي, 2020)
ظهرت في الآونة الأخيرة ظاهرة عدم التمييز والفصل بين حرية التعبير المحمية قانونا والمشروعة وبين خطاب الكراهية الذي يترتب عليه في معظم الأحوال انتهاك لحقوق الآخرين. بالرجوع إلى مختلف الوثائق الدولية يلاحظ أنها قد تناولت الحق في حرية التعبير باعتباره حقا مقدسا وجب على الجميع احترامه وعدم المساس به، لكن المبالغة في استعمال هذا الحق استدعت إلى تقييده في ظل تنامي خطاب الكراهية وما نجم عنه من أضرار بليغة، ومن هنا جاء تجريم خطاب الكراهية استنادا إلى النصوص الدولية التي أشارت بشكل صريح لهذا التجريم، بل أكثر من ذلك نجد أن المحاكم الجنائية الدولية قد أشارت في أنظمتها الأساسية سواء بصفة صريحة أو ضمنية إلى تجريم خطاب الكراهية، وكل هذا انعكس بدوره على الدول التي اتجهت نحو سن العديد من القوانين تدين ممارسة خطاب الكراهية بجميع صوره. Recently, a phenomenon of non-separation between legitimate freedom of expression, from hate speech which causes violation to the others rights has appeared clearly. Back to the various international documents, it is noted that it has addressed Sacredly the right to freedom of expression that everyone must respect. Nevertheless, the exaggeration in the use of this right called for its restriction in shadow of the growth of hate speech and severe physical or moral damage that resulted. Hence, the hate speech has been explicitly criminalized based on the international texts . Moreover, we find that the international criminal tribunals have indicated the criminalization of hate speech in their statutes, whether explicitly or implicitly. Furthermore, all this in turn has been reflected in countries that have enacted many laws that condemn the practice of hate speech in all its forms.
مجلد4، عدد1
Keywords: حرية التعبير، خطاب الكراهية، التجريم، الاتفاقيات الدولية، المحاكم الجنائية الدولية; freedom of expression; hate speech; criminalization; international conventions; international criminal courts.